Double Standards in the U.S. Foreign Policy: A Comparative Analysis of Approaches to the Ukrainian and Palestinian Conflicts - Belkheir,Elhadj Ahmed; SEDDIKI, Mohamed (Faculty of Letters and Foreign Languages Department of English, 2024)
The international policy of the United States is the approach by which the US deals with foreign countries. The U.S. is still profoundly influential in the world as the main superpower. The creation of a safe and democratic world for the American people and the international community is the primary objective of the United States' foreign policy. Through a comparative analysis, the study reveals how strategic priorities and domestic political pressures significantly shape U.S. responses to international conflicts, frequently resulting in contradictory applications of moral and legal standards. The study uses Ukraine and Palestine as case studies to examine the double standards evident in United States foreign affairs. This work seeks to investigate whether U.S. foreign policy towards Palestine was a double standard. The analysis examines how the inconsistencies in American strategy decisions steadfastly support Ukrainian supremacy despite Russian hostility while at the same time moving Israel's occupation and human rights infringement in Palestine. The outcomes show the more extensive ramifications of these hypocritical standards, especially concerning The American government’s validity in worldwide leadership and global relations. The study additionally addresses what these irregularities mean for The States' diplomatic ties, add to provincial insecurity, and undermine the values of freedom and fundamental human rights that the U.S. claims to maintain on the global stage